Plasma vitamin D is associated with fasting insulin and homeostatic model assessment of insulin resistance in young adult males, but not females, of the Jerusalem Perinatal Study. Issue 7 (13th August 2014) - Moore, Amy; Hochner, Hagit; Sitlani, Colleen M; Williams, Michelle A; Hoofnagle, Andrew N; de Boer, Ian H; Kestenbaum, Bryan; Siscovick, David S; Friedlander, Yechiel; Enquobahrie, Daniel A
Abstract: Objective: To examine cross-sectional relationships between plasma vitamin D and cardiometabolic risk factors in young adults. Design: Data were collected from interviews, physical examinations and biomarker measurements. Total plasma 25-hydroxyvitamin D (25(OH)D) was measured using LC–tandem MS. Associations between 25(OH)D and cardiometabolic risk factors were modelled using weighted linear regression with robust estimates of standard errors. Setting: Individuals born in Jerusalem during 1974–1976. Subjects: Participants of the Jerusalem Perinatal Study ( n 1204) interviewed and examined at age 32 years. Participants were oversampled for low and high birth weight and for maternal pre-pregnancy obesity. Results: Mean total 25(OH)D concentration among participants was 21·7 (sd 8·9) ng/ml. Among males, 25(OH)D was associated with homeostatic model assessment of insulin resistance (natural log-transformed, β =−0·011, P =0·004) after adjustment for BMI. However, these associations were not present among females ( P for sex interaction=0·005). Conclusions: We found evidence for inverse associations of 25(OH)D with markers of insulin resistance among males, but not females, in a healthy, young adult Caucasian population. Prospective studies and studies conducted on other populations investigating sex-specific effects of vitamin D on cardiometabolic risk factors are warranted.